Trap‐Limited Exciton Diffusion in Organic Semiconductors. (19th December 2013) - Mikhnenko, Oleksandr V.; Kuik, Martijn; Lin, Jason; van der Kaap, Niels; Nguyen, Thuc‐Quyen; Blom, Paul W. M.
<x xml:space="preserve">Abstract</x> From time‐resolved luminescence measurements it is demonstrated that the background concentration of excitonquenching defects in a range of organic semiconductors is the same as their electron‐trap concentration. This observation suggests that the exciton‐quenching defects and the electron traps share the same origin. The typical exciton diffusion length of 5–8 nm for organic semiconductors is therefore governed by the distance between the universal electron traps. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>